Thermogravimetric Analysis – A Viable Method for Screening Novel Materials for the Sorbent Enhanced Water-gas Shift Process. (July 2017) - Lundvall, Fredrik; Kalantzopoulos, Georgios N.; Wragg, David S.; Arstad, Bjørnar; Blom, Richard; Sjåstad, Anja Olafsen; Fjellvåg, Helmer
Abstract: Pre-combustion CO2 capture technologies are becoming viable alternatives to more conventional post-combustion capture by gas emissions scrubbing. The sorbent enhanced water-gas shift (SEWGS) process is a promising future technology for CO2 capture. However, the process needs better performing materials than those available today to be competitive against state-of-the-art scrubbing technologies. Layered double hydroxides (LDH) are a promising class of materials to improve the performance of the SEWGS process. These materials have a general formula of M 2+ 1−x M 3+ x (OH)2 (A n− )x/n ·mH2 O, and can be tuned by substituting the metal species, changing the M 2+ /M 3+ ratio, adjusting the synthesis parameters to influence morphology or by adding so-called promotors to improve performance. To aid an ongoing systematic study looking at several of these parameters we have developed a simple yet efficient way of screening materials for further in-depth studies. The method is highly suitable for a typical laboratory setting, and is based on thermogravimetric analysis combined with cyclic exposure to selected gases. In this article we present the results of applying the method to a selection of benchmark materials.